Preoperative 6-minute walk test adds prognostic information to Euroscore in patients undergoing aortic valve replacement. Issue 2 (28th June 2009) - de Arenaza, D P; Pepper, J; Lees, B; Rubinstein, F; Nugara, F; Roughton, M; Jasinski, M; Bazzino, O; Flather, M
Abstract : Aims: The authors investigated the additive prognostic value of the 6-minute walk test (6MWT) to Euroscore in patients with severe aortic stenosis undergoing aortic valve replacement (AVR) Methods and results: 208 patients with severe AS underwent the 6MWT before AVR, as part of a randomised trial (ASSERT) comparing stented and stentless aortic valves. Clinical follow-up was available for 200 patients up to 12 months. The rate of death, myocardial infarction (MI) or stroke (time to first event) was 13% (n = 14) in patients walking <300 metres compared to 4% (n = 4) in those who walked ⩾300 metres (p = 0.017). When rate of death, MI or stroke by Euroscore risk was stratified by 6-minute walking distance, the 6MWT added prognostic information. In a Cox regression analysis 6MWT distance was the only variable retained as an independent predictor of the composite outcome of death, MI or stroke at 12 months (HR 0.28 95% CI 0.09 to 0.85, p = 0.025). Conclusions: The 6MWT is safe and feasible to carry out in patients with severe aortic stenosis before AVR, and provides potentially important functional and prognostic information to clinical assessment and the Euroscore risk score.